(untitled) (International Journal of Biomedical and Advance Research, 2017)
Introduction: Family planning contributes effectively to the social development of a country. This study was carried out to assess the unmet need for contraception among the married women of rural area of Davangere taluk and to determine the factors associated with unmet need for contraception Methods: A community based cross sectional study was conducted among 1020 married women in the reproductive age group 15-49 years of 24 villages in Davangere taluk of Karnataka. They were interviewed using a pre-tested semi-structured questionnaire. Results: The total unmet need was 16.7% with 13.6% for spacing and 3.1% for limiting. The most important reason for unmet need was want of a male child in the future by spouse (63.3%) ignorance (41.6%), and fear of side effect (15.8%). Conclusion: Reducing unmet need is important for helping couples achieve their reproductive goals and for preventing unintended pregnancies that lead to abortion. In order to address the unmet need appropriate counseling for motivation of eligible couples to take up contraception at the earliest is needed.